2020
DOI: 10.23887/jere.v4i3.26989
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Debate Technique towards Eleventh Grade Students’ Speaking Competency

Abstract: Among the four pivotal skills, speaking signifies part of the most essential skill because its role primarily serves as a means of communication. Speaking is an interactive process of developing, creating, constructing and delivering meaning with goal of information exchanges between speaker and hearer. some students still faced some problems to communicate in English. Many students did not show their readiness in speaking English spontaneously.  This study aimed at investigating the significant effect of deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, research conducted (Nainggolan, 2017;Setianingsih et al, 2019;Zainuddin, 2018) found that students' speaking skills in subjects Indonesian can be improved with active debate learning methods. Then, research conducted (Musfirah, 2019;Widiawati & Agustini, 2020) concluded that the application of debating methods can improve students' speaking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research conducted (Nainggolan, 2017;Setianingsih et al, 2019;Zainuddin, 2018) found that students' speaking skills in subjects Indonesian can be improved with active debate learning methods. Then, research conducted (Musfirah, 2019;Widiawati & Agustini, 2020) concluded that the application of debating methods can improve students' speaking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Process skills are a person's skills in using thoughts, reasoning and actions effectively and efficiently (Sumyadi et al, 2020;Elvanisi et al, 2018;Sukmasari & Rosana, 2017). Mathematical sciences and natural sciences have proven successful in developing casual theories that explain important aspects of how the world works (Widiawati & Agustini, 2020;Puspita, 2019;Joffe, 2017). In learning mathematics, one of them is mathematical material that is familiar to students.…”
Section: Introductionmentioning
confidence: 99%